Training police search and rescue teams: Implications for missing persons work - Ferguson, Lorna (Criminology & criminal justice, 2023)
Police search and rescue teams are crucial players in resolving missing person cases. Resultantly, police employ a host of training for search and rescue members in collaboration with institutions, organizations, and groups. Such training, however, has not been studied. This warrants attention as, in a time of police legitimacy crises and austerity policing, appropriate and quality police training for effective, efficient practices is imperative. Therefore, we examined the training needs and offerings for police search and rescue personnel, and their impact on search and rescue operations and work, through thematic analysis of interviews with 52 police search and rescue members from 17 agencies across Canada. Findings suggest there are no homogeneous, structured, or standardized training offerings for police search and rescue personnel. Instead, training varies within and across agencies and regions, and between officers and roles, as it is commonly based upon anecdotal experiences and in-house developed “best practices.” We discuss the implications of these findings for police search and rescue operations and work.